IMPLEMENTASI PENGEMBANGAN KURIKULUM - Azis, Rosmiaty (Inspiratif Pendidikan, 2018)
Abstract: Implementation curriculum is a very decisive component in an educational system, therefore the curriculum is a tool to achieve the education system, therefore the curriculum is a tool to achieve the goals of education and as well as a guide in the implementation of teaching on all types and levels of education, the curriculum is part of a learning process allows learners to know (learning to know), learn to do something (learning to do) to learn to learn and learn to live together (learning to live together). Thus the learning outcomes realize students who are able to membelajarkan on himself, get some knowledge, learners are able to develop in a wider form and can be applied in everyday life.